The Handbook of Hybrid Securities : Convertible Bonds, CoCo Bonds and Bail-In. - Spiegeleer, Jan de (Wiley, 2014)
Introducing a revolutionary new quantitative approach to hybrid securities valuation and risk management To an equity trader they are shares. For the trader at the fixed income desk, they are bonds (after all, they pay coupons, so what''s the problem?). They are hybrid securities. Neither equity nor debt, they possess characteristics of both, and carry unique risks that cannot be ignored, but are often woefully misunderstood. The first and only book of its kind, The Handbook of Hybrid Securities dispels the many myths and misconceptions about hybrid securities and arms you with.